1979
DOI: 10.1104/pp.64.2.220
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide-mediated Oxidation of Indole-3-acetic Acid by Tomato Peroxidase and Molecular Oxygen

Abstract: The oxidation of indoe-3-acetic acid by anionic tomato peroxidase was found to be neglUige unless reaction mixtures were supplemented with H202. The addition of H202 to reaction mixtures initiated a period of rapid indole-3-acetic acid oxidation and 02 uptake; this phase ended and 02 uptake fell to a low level when the H202 was exhausted. The stoichiometry of the reaction, which is highly dependent on enzyme concentration and pH, suggests that H202 initiates a sequence of reactions in which indole-3-acetic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
2

Year Published

1981
1981
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 18 publications
3
27
0
2
Order By: Relevance
“…Nevertheless, IAAoxidases were, at least partially, separated from peroxidases when they were purified from tobacco roots (28), from crown gall tissue culture cells (24), or from mung bean cotyledons (30). In this case (30), IAA oxidation was inhibited by H202 in contrast to the results cited above (9).…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Nevertheless, IAAoxidases were, at least partially, separated from peroxidases when they were purified from tobacco roots (28), from crown gall tissue culture cells (24), or from mung bean cotyledons (30). In this case (30), IAA oxidation was inhibited by H202 in contrast to the results cited above (9).…”
mentioning
confidence: 80%
“…The degradation of auxin by HRP may occur without added cofactors, and in the presence or absence of H202 (6). However, tomato peroxidases are dependent on the presence of H202 for the oxidation of IAA (9) and fail to catalyze the reaction in the presence of compounds such as 2,4-dichloro- 'Present address: Department of Botany. University of Georgia, Athens, GA 30602.…”
mentioning
confidence: 99%
“…The mechanism of oxidation of a plant hormone, IAA has been a subject of investigation by many plant physiologists (126)(127)(128)(129)(130)(131)(132)(133)(134)(135). It is now accepted that free radical species which are formed through catalysis of peroxidase are intermediates in the degradation of IAA (128)(129)(130)(131)(132)(133)(134).…”
Section: Metabolismmentioning
confidence: 99%
“…Kokkinakis and Brooks (14) measured the oxidation of IAA in citrate buffer and found that the tomato enzyme was much less effective than horseradish peroxidase. They subsequently reported that the oxidation by tomato peroxidase was enhanced by the inclusion of peroxide in the reaction mixture (15). The reaction rate decreased sharply when peroxide in the mixture was exhausted.…”
mentioning
confidence: 99%